α-SrZn(5)-Type solid solution, BaZn(2.6)Cu(2.4) - Simura, Rayko (International Union of Crystallography, 2019)

(untitled) (Acta Crystallogr E Crystallogr Commun)
Single crystals of the title compound barium zinc copper, BaCu(2.6)Zn(2.4), were obtained from a sample prepared by heating metal chips of Ba, Cu, and Zn in an Ar atmosphere up to 973 K, followed by slow cooling. Single-crystal X-ray structure analysis revealed that BaCu(2.6)Zn(2.4) crystallizes in an orthorhombic cell [a = 12.9858 (3), b = 5.2162 (1), and c = 6.6804 (2) Å] with an α-SrZn(5)-type structure (space group Pnma). The three-dimensional framework consists of Cu and Zn atoms, with Ba atoms in the tunnels extending in the b-axis direction. Although the Ba atom is larger than the Sr atom, the cell volume of BaCu(2.6)Zn(2.4) [452.507 (19) Å(3)] is smaller than that of α-SrZn(5) [466.08 Å(3)]. This decrease in volume can be attributed to the partial substitution of Cu atoms by Zn atoms in the framework because the Cu—Zn and Cu—Cu bonds are shorter than the Zn—Zn bond. The increase in Ba—Zn interatomic distances from the Sr—Zn distances is cancelled out by the partial replacement of Zn with Cu atoms, which leads to shorter average Ba—Zn/Cu distances.